Performance evaluation of turbulence-accentuated interchannel crosstalk for hybrid fibre and free-space optical wavelength-division-multiplexing systems using digital pulse-position modulation - Mbah, Afamefuna Maduka; Walker, John G.; Phillips, Andrew J. (Institution of Engineering and Technology (IET), 2016)
A hybrid fibre and free-space optical communication link using digital pulse-position modulation (DPPM) in a wavelength-division-multiplexing system is proposed. Such a system, which could provide a power efficient, robust and flexible solution to high-speed access networks, is a contender for a passive optical network solution and could readily be deployed in areas with restrictions in optical fibre installation, or alternatively as a disaster recovery network. Interchannel crosstalk and atmospheric turbulence are major impairments in such a system and could combine in some cases to degrade the system. Both impairments are investigated here and the results are presented in the form of bit error probability, required optical transmission power and power penalties. Depending on the position of the interferer relative to the desired user, power penalties of about 0.2–3.0 dB for weak turbulence and above 20 dB for strong turbulence regimes are reported for bit error rate of 10−6. DPPM scheme with a coding level of 2 show about 2 dB improvements over on–off-keying scheme.